Komunikasi Interpersonal Karyawan Wanita dalam Menumbuhkan Self Efficacy di BSC Café Lubuk Pakam - Utami, Widia Annisa; Rasyid, Abdul (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2024)
Female employees are often the reference and center of the company in maintaining the companys image. Female employees, especially in the industrial sector such as BSC Cafe Lubuk Pakam, often experience communication barriers and lack of self-efficacy. This study aims to determine three things, namely (1) Analysis of the Level of Self Efficacy of Female Employees (2) Integration of Interpersonal Communication to Self Efficacy (3) The Role of Female Employees in Fostering Self Efficacy. This research uses descriptive qualitative research methods case studies with purposive sampling techniques and in-depth interviews. The results of this study indicate that the level of self-efficacy of female employees increases with good communication skills. And female employees themselves have a central role in growing their individual self-efficacy.